Asymmetric Knoevenagel‐Phospha‐Michael Tandem Reaction Synergistically Catalyzed by Achiral Silanols and Grafted Chiral Amines on Mesoporous Silica. Issue 8 (1st July 2019) - An, Zhe; Dai, Yan; Jiang, Yitao; He, Jing
Abstract: Highly efficient and enantioselective asymmetric Knoevenagel‐phospha‐Michael tandem reactions have been achieved on bifunctional heterogeneous catalysts with inherent silanols as acidic sites and immobilized chiral amines as basic sites. Final products were afforded in yields of up to 99% and ee values of up to 99%. The effects of substituents on benzaldehyde and molecular dimensions of phosphites have also been investigated. Larger substrates can access the catalytic site inside larger mesoporous pores, thereby improving both of yield and ee of final products. Abstract : Locked wheels : Highly efficient and enantioselective asymmetric Knoevenagel‐phospha‐Michael tandem reactions have been achieved on bifunctional heterogeneous catalysts with inherent silanols as acidic sites and immobilized chiral amines as basic sites.